English collocations extracted from a corpus of university learners and its contribution to a language teaching pedagogy - doi: 10.4025/actascilangcult.v34i2.17130 - Orenha-Ottaiano, Adriane (Acta Scientiarum. Language and Culture, 2012)
Taking into consideration the relevance of foreign language teaching and the learning of collocations (ALTENBERG; EEG-OLOFSSON, 1990; FONTENELLE, 1994; MEUNIER; GRANGER, 2008), this paper aims at showing results of an investigation on whether the teaching of collocations should be implicit or explicit to the Brazilian university students. Furthermore, the research has the purpose of presenting some collocational aspects from a corpus of the written language learners made up of intermediate, upper intermediate and advanced university students’ argumentative essays at a public university in Brazil. With the help of WordSmith Tools (SCOTT, 2007), it was possible to raise students’ most frequent collocational choices and patterns, the most/least used type of collocations, the influence of the mother tongue on their choices, among other aspects. With the purpose of motivating and involving students in classroom research, it was also introduced The Corpus of Contemporary American English (COCA), created by Mark Davies. By doing so, students could compare their collocational choices with the patterns found in the online corpus, extract more collocational patterns and, consequently, be aware of the potential of corpora for the foreign learning process, specifically for raising language awareness, with focus on prefabricated chunks.